2017
DOI: 10.1124/jpet.117.244319
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor Agonist, 2-p-(2-Carboxyethyl)phenethylamino-5′-N-ethylcarboxamidoadenosine Hydrochloride Hydrate, Inhibits Inflammation and Increases Fibroblast Growth Factor-2 Tissue Expression in Carrageenan-Induced Rat Paw Edema

Abstract: Adenosine is the final product of ATP metabolism, mainly derived from the action of 5'-nucleotidase cleavage of AMP. Cellular production of adenosine is greatly enhanced in inflamed tissues, ischemic tissues, and under hypoxia, where ATP is released from damaged cells. Much evidence has been accumulated on adenosine anti-inflammatory effects mediated through A receptor activation; A adenosine receptor has also been shown to play a role in matrix deposition and wound healing in a damaged tissue, contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…However, A 2A R exerted opposite effects on the peripheral and central nervous systems. A 2A R activation in the peripheral system usually showed anti‐inflammatory effects and A 2A R agonists had beneficial effects on asthma and wound healing 37,38 . In contrast, A 2A R inhibition revealed neuroprotective effects in many CNS diseases including TBI, AD, and PD 39–42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, A 2A R exerted opposite effects on the peripheral and central nervous systems. A 2A R activation in the peripheral system usually showed anti‐inflammatory effects and A 2A R agonists had beneficial effects on asthma and wound healing 37,38 . In contrast, A 2A R inhibition revealed neuroprotective effects in many CNS diseases including TBI, AD, and PD 39–42 .…”
Section: Discussionmentioning
confidence: 99%
“…A 2A R activation in the peripheral system usually showed anti‐inflammatory effects and A 2A R agonists had beneficial effects on asthma and wound healing. 37 , 38 In contrast, A 2A R inhibition revealed neuroprotective effects in many CNS diseases including TBI, AD, and PD. 39 , 40 , 41 , 42 Our group had reported that the opposite effects of A 2A R were associated with the extracellular glutamate concentrations.…”
Section: Discussionmentioning
confidence: 99%